Pengaruh Kepemimpinan Servant Terhadap Budaya Sekolah pada UPTD SDN No 076715 Siana’a Kecamatan Mandrehe Kabupaten Nias Barat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of servant leadership on school culture at UPTD SDN No. 076715 Siana’a, Mandrehe Subdistrict, West Nias Regency. Servant leadership is a leadership style that emphasizes serving others, particularly team members, before considering the leader’s personal interests. The school culture referred to in this research includes the values, norms, and positive habits that are applied and developed within the school environment. This research uses a quantitative method with data collected through the distribution of questionnaires to predetermined respondents. The results show that servant leadership has a significant influence on school culture. Based on the results of the coefficient of determination test, the Adjusted R Square value is 0.443. This indicates that the servant leadership variable (X) can explain the school culture variable (Y) by 44.3%, while the remaining 55.7% is explained by other variables outside this study. These findings suggest that the higher the application of servant leadership, the better the school culture that is formed in the environment of UPTD SDN No. 076715 Siana’a.